A Simulation Study on Warpage Analysis of Injection Moulded Plastic Part - Sanam Shikalgar; Mahesh Zope; Pratik Sonawane; Deepti Marathe (International Journal of Engineering and Management Research, 2021)
A part to be injection molded is evaluated by simulation for warpage analysis. The plastic part is a supporting plate to be used in the oil filter and it’s made out of nylon material. The effect of various parameters from design to processing of plastic parts is considered and validated by simulation results. The research involved in this was designing mould, computer-aided engineering, simulation analysis, and determination of plastic part processing conditions. In this work PA66 (Grade name – Zytel 70G13HS1LNC010) material is used and the material contains 13 % of fiber. Fiber orientation is nothing but the distribution of plastic melt inside the cavity and it also plays important role in deciding the warpage of part. The effect of process parameters on part warpage is investigated from various aspects in comparison with the conventional runner system. Hot runner mould system with innovative cooling channel designs is good results-driven. Results of simulations reveal that elevated mould temperature reduces the unwanted freezing time during the injection phase and thus improves mouldability and enhances part quality. Under similar mould temperature conditions, the effect of process parameters on warpage decreases according to the following order, packing time, packing pressure, melt temperature, injection pressure, and cooling time respectively.